A General Theory of Social Impact Accounting: Materiality, Uncertainty and Empowerment. Issue 2 (4th May 2018) - Nicholls, Alex
ABSTRACT: This paper argues that social impact accounting is different from financial accounting practice in terms of two key materiality issues: the uncertain nature of its material data; the empowering processes by which materiality is established. Drawing upon some detailed empirical analysis, this paper develops a new general theory of social impact accounting to suggest that successful social impact accounting processes both give voice to service users and produce more accurate performance data. The paper advances research in both social impact accounting and in critical approaches to accounting more generally.